The Implementation of Problem-based Learning: Students' Mastery of the Adverb Clause of Reason - Annisa Nur Azizah; Darmawan Darmawan; Siska Bochari (Universitas Cokroaminoto Palopo, 2022)
This study aimed at finding out whether or not Problem-based Learning (PBL) can improve the mastery of adverb clause of reason, specifically focused on subordinating conjunctions: because, since, and now that. They seemed easy to use, but students had difficulty identifying the conjunctions used in sentences and constructing complex sentences that are necessary for including those conjunctions. One pre-test and post-test research design was used with 45 populations of MA Alkhairaat Ampibabo eleventh-grade students. Purposive sampling was used to select the sample, which consisted of 24 students from the XI science class. The data were collected using tests consisting of pre-test and post-test and analyzed statistically using t-test. The result of the data analysis shows that the value of t-counted (7.49) is higher than the t-table (1.714) by applying a significance level of 0.05 with a degree of freedom (df)=23. It implies that PBL has positively improved students’ mastery of the adverb clause of reason. In terms of subordinating conjunctions, the conjunction now that has the most errors in both the pre-test and post-test, followed by the conjunction since, and finally the conjunction because.